2017
DOI: 10.1002/star.201600317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preprocessing at low or ultralow temperatures combined with sodium alginate on retrogradation properties of normal cornstarch during chill storage

Abstract: In this research, normal cornstarch (NCS) was preprocessed at low and ultralow temperatures, both with and without the addition of sodium alginate (AG), and then stored at 4 °C for 14 days to evaluate the retrogradation properties. The results showed that preprocessing with low (−18 °C) or ultralow (−80 °C) temperature could reduce the gel hardness, retrogradation enthalpy (ΔHr), the ratio of intensity at a value of 1047–1022 cm−1 (R1047/1022), and the relative crystallinity (RC) value of NCS. These four param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…As stored for 21 days, the RR i values of PS and SPS were 27.1% and 22.9%, respectively. Similar results have been reported that the presence of xanthan gum, CMC, AG, green tea polysaccharide, or b-cyclodextrin could reduce the RR i or DH ret value of starches (Han, Kang, Bai, Xue, & Shi, 2018;Li, Wang, Chen, Liu, et al, 2017;Tang et al, 2013;Tian et al, 2009;Xiao et al, 2013;Zhou et al, 2008). The RR i values of all samples increased with prolonging storage time.…”
Section: Thermal Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…As stored for 21 days, the RR i values of PS and SPS were 27.1% and 22.9%, respectively. Similar results have been reported that the presence of xanthan gum, CMC, AG, green tea polysaccharide, or b-cyclodextrin could reduce the RR i or DH ret value of starches (Han, Kang, Bai, Xue, & Shi, 2018;Li, Wang, Chen, Liu, et al, 2017;Tang et al, 2013;Tian et al, 2009;Xiao et al, 2013;Zhou et al, 2008). The RR i values of all samples increased with prolonging storage time.…”
Section: Thermal Propertiessupporting
confidence: 87%
“…This suggested that the addition of AG could delay the retrogradation of all starches. Similar results have been reported that the presence of xanthan gum, CMC, AG, green tea polysaccharide, or b-cyclodextrin could reduce the RR i or DH ret value of starches (Han, Kang, Bai, Xue, & Shi, 2018;Li, Wang, Chen, Liu, et al, 2017;Tang et al, 2013;Tian et al, 2009;Xiao et al, 2013;Zhou et al, 2008). It is likely that hydrocolloids can block the starch recrystallization due to the effective competition for available water against starch granules (Phimolsiripol et al, 2011;Tang et al, 2013).…”
Section: Thermal Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…Starch is an important component of cereal products that is the major energy source for people in the developing countries (Li et al., 2017). When being heated in water, the starch granules began to absorb water, then swelled and ruptured, and underwent an irreversible transition from ordered to disordered structures.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) revealed that the sodium dodecyl sulfate as a surfactant showed a more retardant effect on the retrogradation of glutinous rice gels as compared to the non‐starch hydrocolloids (carrageenan, konjac, xanthan, sodium alginate, locust bean gum, and guar gum). In our previous study, we suggested that the addition of sodium alginate could retard the retrogradation of normal cornstarch, potato starch, and sweet potato starch (Yu, Wang, Chen, and Li, 2018), and the retardant effect exhibited a positive correlation to the sodium alginate concentration (Li et al., 2017). Our another work also found that the addition of stearic acid and sodium alginate mixtures showed a better retardant effect on the wheat starch retrogradation, as compared to the samples with adding stearic acid alone or sodium alginate alone.…”
Section: Introductionmentioning
confidence: 99%